2010
DOI: 10.1016/j.juro.2010.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and Serum Carbohydrate Antigen 19-9 as a Biomarker in Ureteropelvic Junction Obstruction in Children

Abstract: Voided urine carbohydrate antigen 19-9 is a noninvasive, clinically applicable marker in congenital obstructive nephropathy. The practical implications of these data for diagnosis and long-term followup in ureteropelvic junction obstruction are significant. Our findings suggest that proper decrease in urinary carbohydrate antigen 19-9 after pyeloplasty is predictive of excellent surgical outcomes and resolution of renal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 14 publications
7
28
1
8
Order By: Relevance
“…A limited number of studies report the use of urinary or serum CA 19-9 levels as biomarkers in the early identification and serial assessment of UPJ obstruction. Kajbafzadeh et al [21] have recently reported an increase of CA 19-9 levels in serum, urine, and intrarenal cyst fluids of children with obstructive pathology. Given that the serum CA 19-9 level is a sensitive marker for malignancies and some other benign conditions involving epithelial structures, they suggested that serum CA 19-9 had a low sensitivity for predicting urinary obstruction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A limited number of studies report the use of urinary or serum CA 19-9 levels as biomarkers in the early identification and serial assessment of UPJ obstruction. Kajbafzadeh et al [21] have recently reported an increase of CA 19-9 levels in serum, urine, and intrarenal cyst fluids of children with obstructive pathology. Given that the serum CA 19-9 level is a sensitive marker for malignancies and some other benign conditions involving epithelial structures, they suggested that serum CA 19-9 had a low sensitivity for predicting urinary obstruction.…”
Section: Discussionmentioning
confidence: 98%
“…The result may suggest that voided urine CA 19-9 levels may be useful for identifying obstructions in hydronephrosis patients. Kajbafzadeh et al [21] showed that the urinary CA 19-9 level with a cut-off of 30.6 U/mL was 100% sensitive and 82.6% specific, indicating a very good diagnostic profile in congenital UPJ obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…A presença de hidronefrose foi correlacionada ao aumento CA 19-9 sérico e urinário em poucos estudos clínicos (Suzuki et al, 2002;Aybek et al, 2006;Akgül et al, 2007;Kajbafzadeh et al, 2010). Não existem estudos experimentais na literatura avaliando o comportamento do CA 19-9 em modelo de obstrução ureteral.…”
Section: Discussionunclassified
“…Demonstraram também que a função renográfica inicial apresentou correlação inversa com CA 19-9 da urina intrapélvica e com CA 19-9 urinário da bexiga, mas ressaltaram que a exceção a esse padrão ocorreria em rins severamente obstruídos com lesão renal extensa (Kajbafzadeh et al, 2010). Foi feita a hipótese de que apesar de níveis elevados do CA 19-9 na urina da pelve renal, devido à drenagem prejudicada e falta de clearance tubular adequado, os níveis de CA 19-9 na urina vesical seriam muito baixos.…”
Section: Discussionunclassified
See 1 more Smart Citation